Efektivitas Kebijakan Earmarking Tax Atas Pajak Rokok Dalam Upaya Kesehatan Masyarakat di DKI Jakarta Tahun 2018 - 2020 - Asih Wulan Sari; Mainita Hidayati (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Indonesia’s earmarking policy on cigarette taxes is stated in Law No. 28 of 2009 Article 31. The application of the cigarette tax is intended to protect the public from the dangers of smoking and provide optimal health services to the people. Since the beginning of Covid-19 pandemic, tobacco control programs, especially health screening activities for school children, had to be stopped. In addition, the government has also relocated the budget for handling Covid-19 cases in DKI Jakarta, causing regional revenues to decrease. This study was conducted using a descriptive qualitative method with the aim of analyzing the effectiveness of the earmarking policy on smoking taxs in maintaining public health in DKI Jakarta in 2018–2020. The results show that based on Mardiasmo's theory of effectiveness which involves indicators of output, outcome and objective, the earmarking policy on cigarette taxes in DKI Jakarta can be categorized as effective in maintaining public health. This is seen from the level of tax earmarking which reached 97.93% in 2018, 99.80% in 2019, and 75.83% in 2020. The use of funds from cigarette tax earmarking is right on target, namely to fund health services promotively and preventively as well as funding health insurance programs. However, tobacco control activities in DKI Jakarta have not been effective in achieving the target because there are no clear regulations related to the program. As a result, changes in smoking behavior in the community are not too significant.